CRF-5-HT interactions in the dorsal raphe nucleus and motivation for stress-induced opioid reinstatement - Li, Chen (Psychopharmacology (Berl), 2020)
RATIONALE: The serotonin (5-hydroxytryptamine, 5-HT) system plays an important role in stress-related psychiatric disorders and substance abuse. Our previous data show that stressors can inhibit 5-HT neuronal activity and release by stimulating release of the stress neurohormone corticotropin-releasing factor (CRF) within the serotonergic dorsal raphe nucleus (DRN). The inhibitory effects of CRF on 5-HT DRN neurons are indirect, mediated by CRF-R1 receptors located on GABAergic afferents. OBJECTIVES: We tested the hypothesis that DRN CRF-R1 receptors contribute to stress-induced reinstatement of morphine conditioned place-preference (CPP). We also examined the role of this circuitry in stress-induced negative affect with 22 kHz distress ultrasonic vocalizations (USVs), which are naturally emitted by rats in response to environmental challenges such as pain, stress, and drug withdrawal. METHODS: First, we tested if activation of CRF-R1 receptors in the DRN with the CRF-R1-preferring agonist ovine CRF (oCRF) would reinstate morphine CPP and then if blockade of CRF-R1 receptors in the DRN with the CRF-R1 antagonist NBI 35965 would attenuate swim stress-induced reinstatement of morphine CPP. Second, we tested if intra-DRN pretreatment with NBI 35965 would attenuate foot shock stress-induced 22 kHz USVs. RESULTS: Intra-DRN injection of oCRF reinstated morphine CPP, while intra-DRN injection of NBI 35965 attenuated swim stress-induced reinstatement. Moreover, intra-DRN pretreatment with NBI 35965 significantly reduced 22 kHz distress calls induced by foot shock. CONCLUSIONS: These data provide evidence that stress-induced negative affect is mediated by DRN CRF-R1 receptors and may contribute to reinstatement of morphine CPP.